Tibial Plasmablastic Lymphoma in a HIV-Negative Child: A Novel Extraoral Localisation - Mala, Ali; Khan, Yameena Noman; Ahmed, Akbar; Khayyam, Naema; Aftab, Kanwal (Case Reports in Hematology, 2022)
Plasmablastic lymphoma is an aggressive, high-grade non-Hodgkin lymphoma predominantly seen in HIV-infected individuals. Alongside a strong correlation with HIV, PBL can manifest in immunocompromised HIV-negative patients. A rare case of PBL in an immunocompetent and otherwise healthy child presented to Indus Hospital & Health Network (IHHN), Karachi, Pakistan. The patient had complaints of swelling and pain in the right leg and was referred from a city in Interior Sindh. Histopathological analysis revealed sheets and aggregates of neoplasm replacing bone marrow interspersed with sclerotic bony fragments. Large, monomorphic, multinucleated neoplastic cells containing abundant cytoplasm and scattered pleomorphic cells were also noted, leading to the diagnosis of tibial plasmablastic lymphoma. A FAB/LMB96 group C chemotherapy regimen for aggressive and high-risk cancer was administered with a marked improvement in clinical symptoms.